P07 Media constructions of 'arthritis': a mixed Methods qualitative study. (13th September 2016) - Rowley, R; Jinks, C; Richardson, JC
Abstract : Background: Musculoskeletal conditions, including arthritis, have a global impact, causing increased disability and reduced quality of life. Previous research has demonstrated negative attitudes and beliefs about arthritis exist which means the condition is often undermanaged and deprioritised. One potential influence on such attitudes is the media. Understanding how the media constructs arthritis, and what impact media constructions have on perceptions of arthritis, will shed light on factors that influence attitudes and management of the condition in everyday life. Methods: This research aimed to investigate media constructions of arthritis. Mixed Methods were used, including media analysis of highest circulating newspapers (n = 11) and magazines (n = 3), and focus groups (n = 2) to explore reception of media messages. Results were analysed using a combination of thematic, discourse and imagery analyses. Results: A total of 1014 newspaper and 18 magazine articles were analysed. Arthritis was conceptualised in three ways – as a disease, condition or ailment. As such, arthritis was not presented as a singular condition; instead the construction, enactment and reality of arthritis were multiple. These multiple conceptualisations were shaped by wider social issues, such as understandings of disability (saints or scroungers) and ageing (peril or promise), and their representation in the media was determined by factors of media production (audience targeting, commercial interests and 'newsworthiness'). The focus group findings reflected these perceptions, as well as illustrating that media trust and credibility influence how media messages are received and interpreted by the general public. Conclusion: Recognising arthritis as multiple is important for health care professionals and patients, as the multiple conceptualisations can impact on how arthritis is enacted, and may affect perceptions of legitimacy and deservedness. Media representations of arthritis may lead to the condition being deprioritised and could present a barrier to the uptake of self-management strategies recommended in current guidelines.